Mixed Co-Mn oxide-catalysed selective aerobic oxidation of vanillyl alcohol to vanillin in base-free conditions - Jha, Ajay; Patil, Kashinath R.; Rode, Chandrashekhar V. (Chempluschem, 2013)
Manganese-doped cobalt mixed oxide (MnCo-MO) catalyst was prepared by a solvothermal method. The as-prepared catalyst was characterised by X-ray photoelectron spectroscopy, H-2 temperature-programmed reduction, O-2 temperature-programmed oxidation and XRD. This catalyst gave 62% conversion with 83% selectivity to vanillin in 2hours for the liquid-phase air oxidation of vanillyl alcohol without using base. Three different types of metal oxides were observed in the prepared catalyst, which could be identified as Co3O4, Mn3O4 and CoMn2O4. Among these, the tetragonal phase of CoMn2O4 was found to be more active and selective for vanillyl alcohol oxidation than Co3O4 and Mn3O4. High-resolution TEM characterisation revealed the morphology of MnCo-MO nanorods with a particle size of 10nm. Successful recycling of the catalyst was also established in this oxidation reaction.
Keywords: aerobic oxidation; cobalt; heterogeneous catalysis; manganese; spinel phases